استخدام التقنيات الحديثة للذكاء الاصطناعي في الدول العربية - دقعة، أحمد; حنيش ،أحمد (جامعة الوادي University of Eloued, 2024)
تهدف هذه الورقة البحثية إلى إبراز الجهود المبذولة من طرف الدولة الجزائرية من اجل الاعتماد على تقنيات الذكاء الاصطناعي في مجال تحقيق التنمية الاقتصادية، وكذلك إبراز أهم التحديات التي يواجهها تطبيق الذكاء الاصطناعي في الجزائر، خاصة الصعوبات المتمثلة في البنية التحتية في مجال حصر البيانات الضخمة التي يحتاجها الذكاء الاصطناعي، وأيضا إلى التشريعات والقوانين المنظمة إلى هذه التقنية، كما تتناول هذه الدراسة إلى تقديم أهم الجهود التي تبذلها الجزائر من اجل تذليل الصعوبات والعراقيل من اجل تطبيق الذكاء الاصطناعي في مجال التنمية الاقتصادية، وقد خلصت الدراسة الى انه بإمكان الجزائر الدخول الى عالم التكنولوجيا من بابها الواسع اذا عرفت كيف توظف تقنيات الذكاء الاصطناعي، والاهتمام بالمعرفة والبحث العلمي، والاستغلال الأمثل لمواردها البشرية. This research paper aims to highlight the efforts made by the Algerian state to rely on artificial intelligence technologies in the field of achieving economic development, as well as highlighting the most important challenges facing the application of artificial intelligence in Algeria, especially the difficulties represented in the infrastructure in the field of limiting the big data needed by artificial intelligence, and also the legislation and laws regulating this technology. This study also addresses the most important efforts made by Algeria to overcome the difficulties and obstacles in order to apply artificial intelligence in the field of economic development. The study concluded that Algeria can enter the world of technology through its wide door if it knows how to employ artificial intelligence technologies, pay attention to knowledge and scientific research, and make optimal use of its human resources.
The Use Of Modern Artificial Intelligence Technologies In Arab Countries ( A Case Study of Algeria )
Keywords: الذكاء الاصطناعي; التنمية الاقتصادية; البيانات الضخمة; artificial intelligence; economic development; the big data